The Influence of Regional Revenue, Balancing Funds, Special Autonomic Funds, and Economic Growth on Capital Expenditures Allocation - Eva Jumiati; Mirna Indriani; Darwanis Darwanis (Universitas Syiah Kuala, 2019)
Objective – This study aims to examine the effect of Regional Revenue, Balancing Funds, Special Autonomy Funds, and Economic Growth on the Allocation of Capital Expenditures in Regencies / Cities in Aceh for the period 2013-2017. Design/methodology – This type of research is quantitative, the population of this study is all districts/cities in Aceh in 2013-2017, amounting to 23 local governments consisting of 18 district governments and 5 city governments. The unit of analysis of this research is the Realization Report of the Revenue and Expenditure Budget (LRA-APBK) in Aceh for the 2013-2017 Period which has been audited by the Financial Supervisory Agency (BPK) and Gross Regional Domestic Product (PDRB) data. Results – The results of the study show that both jointly and separately, regional own-source revenues, balancing funds, special autonomy funds, and economic growth have an effect on the allocation of capital expenditures in districts/cities in Aceh for the period 2013-2017. Originality/Value – Discussion related to the influence of special autonomy funds on capital expenditure is limited research, so it is deemed necessary to do as additional insight and reference of research results.